2016
DOI: 10.1016/j.bbrep.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

A novel tag-free probe for targeting molecules interacting with a flavonoid catabolite

Abstract: 3,4-Dihydroxyphenylacetic acid (DOPAC) is one of the colonic microflora-produced catabolites of quercetin 4′-glucoside (Q4′G). Although the interaction of DOPAC with cellular proteins might be involved in its biological activity, the actual proteins have not yet been identified. In this study, we developed a novel tag-free DOPAC probe to label the targeted proteins by the copper(I)-catalyzed azide alkyne cycloaddition (CuAAC) and verified its efficacy. Various labeled proteins were detected by the DOPAC probe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…24) Our group has successfully detected the direct modification of Keap1 and AhR by DOPAC using its click chemistry probe and the pull down assay. 15) These results indicated that covalent modification of Keap1 and AhR by DOPAC might be involved in the activation of these pathways and upregulation of ALDH genes in Hepa1c1c7 cells. DOPAC not only induced the gene expression of ALDHs, but also the phase 2 genes including glutathione S-transferase, 25) heme oxygenase-1 and glutamate-cysteine ligase, catalytic subunit, 6) both of which play an effective role in protection against oxidative stress.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…24) Our group has successfully detected the direct modification of Keap1 and AhR by DOPAC using its click chemistry probe and the pull down assay. 15) These results indicated that covalent modification of Keap1 and AhR by DOPAC might be involved in the activation of these pathways and upregulation of ALDH genes in Hepa1c1c7 cells. DOPAC not only induced the gene expression of ALDHs, but also the phase 2 genes including glutathione S-transferase, 25) heme oxygenase-1 and glutamate-cysteine ligase, catalytic subunit, 6) both of which play an effective role in protection against oxidative stress.…”
Section: Resultsmentioning
confidence: 74%
“…21) AhR has been identified as a potential target of covalent modification by DOPAC. 15) Expectedly, DOPAC significantly increased the nuclear level of the AhR proteins (Fig. 3(A) and (B)).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Similar to the bacterial metabolism of daidzein, sesame lignans and ellagitannins are converted into enterolactone / enterodiol and urolithin A, respectively, all of which can bind to estrogen receptors [59]. Ring-fission catabolism has been observed in the case of tea catechins, the primary class of flavonoids in green tea; γ-valerolactones have been identified in human urine after green tea ingestion ( Figure 2 targets of covalent modification by DOPAC in mouse hepatoma cells [77]. Thus, even though DOPAC shows relatively weaker biological activities than quercetin aglycon [72,76], DOPAC is quite plausibly a main component that facilitates the health-promoting potential of quercetin glycosides.…”
Section: Ring-fission Products Of Polyphenolsmentioning
confidence: 97%
“…3,4-Dihydroxyphenylacetic acid, a breakdown product from quercetin glycosides, could be absorbed into the circulation and show biological activities through electrophilic adduction of the corresponding quinone to biomolecules. ( 19 )…”
Section: Generation Of Quinones and Reaction Toward Biomoleculesmentioning
confidence: 99%